Haematological stress indicator of layer chickens in open sided and closed house systems - Kadir, Julailiyani (2015)
Layer hens in Malaysia are raised in different types of housing, such as open sided house and closed house system. Previous studies have shown layer hens raised in different housing systems experienced different levels of stress. Thus, this study was conducted to evaluate the heterophil to lymphocyte ratio (stress indicator) of layer hens raised in open sided and close house systems. A total of 120 Lohmann Brown birds were chosen randomly and equally (n=20) from two housing types comprised of three open sided houses and three closed houses. Blood samples were obtained once from the birds for the determination of the heterophil to lymphocyte (H/L) ratio. The environmental parameters include temperature, relative humidity and air velocity were taken in the morning, afternoon and evening on the same day of blood sampling. The heat stress index was calculated by the sum of the temperature and the relative humidity. During sampling, two of six houses, both were open sided houses, were not contracted with disease outbreaks (viral infection). Results showed that H/L ratio of unhealthy birds in the open sided houses was significantly (p<0.05) higher (1.113) compared to the healthy birds (0.646) reared in the similar house type. Meanwhile, the H/L ratio of unhealthy birds in the open sided house was significantly (p<0.05) higher (1.113) as compared to the unhealthy birds in the closed house system (0.836). Although the heat stress index for both types of houses was not exceeded the limit, which is 107 oC, the mean value of air velocity in the open sided houses was significantly (p<0.05) lower (0.4 m/s) compared to closed houses (1.8 m/s). Hence, it is suggested that low air velocity in the open sided houses contributed to the ineffective heat regulation by the birds via convection, which lead to stress and caused H/L elevated. Results in this study showed that H/L ratio is a good haematological stress indicator in layer hens, and unhealthy birds particularly the one that reared in an open sided house had higher H/L ratio indicating a greater stress response.